Tingkat Kemampuan Berfikir Reflektif Siswa Sekolah Dasar Kelas Tinggi - Novy Trisnani (AR-RIAYAH : Jurnal Pendidikan Dasar, 2020)
The ability to think reflective is an important ability to be developed in the mathematics learning process because it contains critical thinking skills and creative thinking skills. The purpose of this study was to assess the level of reflective thinking skills of elementary school students in high grades. This type of research is library research. The research data was obtained through a review of literature sources, including literature from print and online research journals, proceedings, reference books according to topics, modules, and other relevant sources. The ability to think reflective of elementary school students in high grades includes, first mentioning things in basic knowledge what is asked in the questions, what is known, mentioning the relationship between what is asked and what is known, and so on. Second, displaying problem-solving ideas designed according to known knowledge. Third, look back at the problem solving that has been made in order, including correcting and explaining if there is an error from the answer, and making conclusions correctly